Factors Affecting the Sustainability of Halal MSMEs in Yogyakarta: A Study on Literacy, Digitalization, and Fintech - Muhammad Faqih Maskuri; Ahmad Febriyanto; Hilmy Baroroh; Shulhah Nurullaily (Diponegoro Journal of Economics, 2024)
This study aims to determine whether financial literacy, digital marketing, financial technology, and financial management affect the sustainability of halal MSMEs in Yogyakarta. This quantitative study uses primary data collection methods through online and offline questionnaires. The sampling technique was a purposive sampling method with a total of 110 respondents who were Halal MSME players in Yogyakarta. The results showed that the four independent variables, namely financial literacy, digital marketing, financial technology, and financial management, had a significant positive effect on the sustainability of halal MSMEs in Yogyakarta. Research related to the sustainability of the performance of halal MSMEs in Yogyakarta has not been widely explored by experts. To the best of the author’s knowledge, studies focusing on the sustainability performance of halal SMEs are still rare, and this literature can complement the exploration of the sustainability of the performance of halal MSMEs, especially in the Yogyakarta area.